(untitled) (Research, Society and Development, 2021)
The risks in elderly people with tuberculosis are high, which is why pharmaceutical assistance in this type of patient is important, with the pharmacist being the most qualified professional to support drug interventions when there is resistance to treatment. The study aimed to relate the role of the pharmacist in supporting elderly people with resistance to tuberculosis treatment. The study is a literature review, where the bibliographic research method was used, due to the possibility of analyzing references published in studies already carried out for the collection of ample information and previous knowledge about the subject. For the study survey, Books, Magazines, Brazilian Societies Guidelines, articles in the SciELO, PubMed/MEDLINE research databases were used. Resistance to treatment was found to be a threat to the health system, as it can lead to increased length of hospital stay, functional decline, increased spending on health and mortality from all causes. The effectiveness of the treatment will depend on the patient’s discipline and knowledge about the correct use of drugs, in addition to an understanding of the benefits that the treatment provided in the way it is prescribed and guided by the doctor. Thus, having the pharmacist in the care practice with the development of strategies that can promote the education and awareness of the elderly in relation to the treatment is of great importance for the control and minimization of the disease’s complications.